DEVELOPMENT OF CLINICAL SCENARIO’S INFORMATION MODEL IN THE MEDICAL SIMULATION CENTER - I. V. Tolmachyov; Ye. G. Ripp; S. V. Tropin; Ye. V. Karpushkina; A. S. Tsverova (Бюллетень сибирской медицины)
There is the big issue in medical education which is students don’t have enough skills. Often even with theoretical knowledge graduate medical students need to improve their skills by working with patients. Obviously it can be a risk for patients and takes quite long time. This situation could be changed with applying simulation technologies in medical education. Medical education with virtual simulators allows reducing the time of skills development and improving the quality of training. The aims of this work are developing informational model and creating clinical scenarios of emergency states in the Medical Simulation Center.Objectives:– to analyze the process of scenario conducting;– to create clinical scenarios of emergency states (anaphylactic shock, hypovolemic shock, obstructive shock) with specialist’s help.The scenarios consist of sections such as main aim, skills, required mannequins, preparation of the mannequins, preparation of medical equipment and instruments for the scenario, preparation of special materials, scenario description, guide for operator, information for trainees.By analyzing the process of scenario conducting the key participants were defined who are operator, assistant, trainer, trainees. Also the main scenario stages were defined. Based on the stages diagram of variants of scenario conducting was designed.As an example there are fragments of scenario “Obstructive shock – a pulmonary embolism” in this article. Learn skills are cognitive, technical, social ones.Results. This paper presents an analysis of the clinical scenario conducting. Information model was developed which based on object-oriented decomposition. The model is the diagram of variants of scenario conducting. Scenario’s structure for emergency states was formulated. The scenarios are anaphylactic shock, hypovolemic shock, obstructive shock (pulmonary embolism, tension pneumothorax), pulmonary edema, hypertensive crisis, respiratory distress syndrome of the newborn, meconium aspiration syndrome.